Increasing the fatigue strength of laser-powder bed fusion manufactured Ti6Al4V hip stems by means of appropriate post-treatments - Schröder, Stefan; Gibmeier, Jens; Mai, Phuong Thao; Fischer, Maximilian C. M.; Innmann, Moritz Maximilian; Renkawitz, Tobias; Kretzer, Jan Philippe (Journal of the mechanical behavior of biomedical materials, 2026)
Due to the lower fatigue resistance of LPBF manufactured Ti6Al4V alloy compared to wrought material, hip stems are still manufactured conventionally, despite the advantages of patient-specific joint replacements. Therefore, the aim of the study was the investigation of appropriate post-treatments to increase the fatigue resistance of LPBF manufactured Ti6Al4V alloy using a four-point bending setup and a Locati-test. The results showed that only a combination of a hot isostatic pressing process and a sufficient surface treatment can lead to similar fatigue results as wrought material. Thereby, machining, deep rolling and shot peening turned out to be suitable surface treatments. For complex geometries like hip stems, shot peening is the most sufficient surface treatment. A combined surface treatment of shot peening and polishing led to similar fatigue results as the shot peening process alone. It can be followed that a combination of shot peening with a previous hot isostatic pressing process leads to satisfying fatigue results comparable to the wrought material and can be applied on complex geometries like hip stems. In addition, shoulder and neck area of a hip stem can be polished after the HIP process and the shot peening procedure without any reduction in fatigue strength.